2018
DOI: 10.1002/2017jd027725
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extensive Urbanization on Summertime Rainfall in the Beijing Region and the Role of Local Precipitation Recycling

Abstract: In this study, we conducted nested high‐resolution simulations using the Weather Research and Forecasting model coupled with a single‐layer urban canopy model to investigate the impact of extensive urbanization on regional precipitation over the Beijing‐Tianjin‐Hebei region in China. The results showed that extensive urbanization decreased precipitation considerably over and downwind of Beijing city. The prevalence of impermeable urban land inhibits local evaporation that feeds moisture into the overlying atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 74 publications
5
42
1
Order By: Relevance
“…Lateral terrestrial water flow‐induced changes in land‐atmosphere interactions are quantified with the recycling methods detailed in section . It is important to note that the estimated regional precipitation recycling rate depends on the specific method applied and is sensitive to various factors including the shape, location, and size of the domain of analysis, as well as the prevailing wind direction and orographic condition (Burde & Zangvil, ; Trenberth, ; Wang, Feng, et al, ). The bulk and E‐tagging methods used in this study are aiming at investigating the changes of the land‐atmosphere interactions induced by the consideration of the lateral terrestrial water flow, rather than quantifying uncertainty of estimated recycling rate caused by the well‐mixed atmosphere and no return flow assumptions (Arnault, Knoche, et al, ; Burde & Zangvil, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lateral terrestrial water flow‐induced changes in land‐atmosphere interactions are quantified with the recycling methods detailed in section . It is important to note that the estimated regional precipitation recycling rate depends on the specific method applied and is sensitive to various factors including the shape, location, and size of the domain of analysis, as well as the prevailing wind direction and orographic condition (Burde & Zangvil, ; Trenberth, ; Wang, Feng, et al, ). The bulk and E‐tagging methods used in this study are aiming at investigating the changes of the land‐atmosphere interactions induced by the consideration of the lateral terrestrial water flow, rather than quantifying uncertainty of estimated recycling rate caused by the well‐mixed atmosphere and no return flow assumptions (Arnault, Knoche, et al, ; Burde & Zangvil, ).…”
Section: Resultsmentioning
confidence: 99%
“…China is undergoing a rapid urbanization process nationwide, and many studies (e.g., Liang & Ding, 2017; Wang et al, 2014; Wang et al, 2018; Yu & Liu, 2015) have demonstrated that urbanization has a great impact on weather and climate in mega cities of eastern China, such as Beijing, Shanghai, and Guangzhou. But rare studies pay attention to the urbanization effect induced by an underdeveloped city in western China.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The WRF model is the most state‐of‐the‐art mesoscale modeling system and widely used around the world, and the WRF model has been coupled with the Noah land surface model and a single‐layer urban canopy model (Kusaka et al, 2001). The coupled WRF/urban canopy model system has been successfully used in urban precipitation simulation (e.g., Wang et al, 2018; Zhong & Yang, 2015). The urban land cover parameterizations include as follows: The building heights are 10, 7.5, and 5.0 m for commercial, high‐intensity residential, and low‐intensity residential, respectively; the fraction of the urban landscape, which does not include the natural vegetation, is setting in default for 0.95 (commercial), 0.9 (high‐intensity residential), and 0.5 (low‐intensity residential).…”
Section: Data and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impact of urbanization on the regional climate of the BTH region has been investigated extensively in recent years (Miao et al, 2009(Miao et al, , 2011Wang et al, 2012Wang et al, , 2015Wang et al, , 2018Xing et al, 2019;L. Yang et al, 2014;C.-L. Zhang et al, 2009), its associated impact on regional NSWS remains poorly quantified.…”
Section: Introductionmentioning
confidence: 99%